Cellulases production optimization and inductors evaluation in pretreated plantain rachis by Penicillium oxalicum - Jiménez Fallas, Marcel Albán (2024)
Pretreated lignocellulosic residues are suitable substrates for cellulases production by filamentous fungi. In the current work, plantain rachis was pretreated with sequential acid and alkali and then used as the main carbon source for cellulases production. First, a full 23 factorial design and response surface methodology (RSM), based on central composite rotatable design (CCRD), were carried out to cellulases production media optimization from plantain rachis by Penicillium oxalicum. The cellulases production was evaluated in flasks and bioreactor scale; in parallel, the addition of possible cellulases inductors was evaluated in flasks: molasses, beer bran, oat bran, and wheat bran. Results from statistical analyses with a level of confidence of 95% demonstrated that the concentration of ammonium sulfate must be kept at 1.625 g/L. The optimum urea and yeast extract concentrations were 0.560 g/L and 0.250 g/L, respectively. Cellulases volumetric productivities were higher in instrumented bioreactor than in flasks: 78.03% for exoglucanase, 10.87% for endoglucanase, 1.58% for β-glucosidase, and 44.36% for FPU. Therefore, P. oxalicum was able to produce cellulases from plantain rachis in flasks and bioreactor, and molasses was the additional inductor that presented an increment in cellulases activities: endoglucanase 15%, exoglucanase 81%, and β-glucosidase 55%.